Postnatal characterization of cells in the accessory olfactory bulb of wild type and reeler mice - Eduardo eMartín-López; Rebeca eCorona; Laura eLopez-Mascaraque (Frontiers Media S.A., 2012)
Olfaction is the most relevant chemosensory sense of the rodents. General odors are primarily detected by the main olfactory system while most pheromonal signals are received by the accessory olfactory system. The first relay in the brain occurs in the olfactory bulb, which is subdivided in the main and accessory olfactory bulb (MOB/AOB). Given that the cell generation time is different between AOB and MOB, and the cell characterization of AOB remains limited, the goal of this work was first, the definition of the layering of AOB/MOB and second, the establishment of cellular phenotypes in the AOB in a time window corresponding to the early postnatal development. Moreover, since reelin deficiency has been related to layering and olfactory learning deficits, those data were compared with reeler mice. Firstly, we compared the layering between AOB and MOB at early embryonic stages. Then, cell phenotypes were established using specific neuronal and glial markers as well as the reelin adaptor protein Dab1 to analyze differences in both genetic backgrounds. There was no apparent difference in the cell phenotypes among AOB and MOB or between wild type and reeler animals. However, it was outstanding a disruption in the granular cell layer of reeler with respect to wild type mice. In conclusion, the AOB in reelin deficient mice showed similar neuronal and glial cell types being only affected the layering of granular cells.